The emperor's new clothes - Rosie Greening (Berkhamsted, Hertfordshire: Make Believe Ideas, 2017)
A retelling of the story of The emperor's new clothes in rhyming text Key sound l-blend spellings: bl, cl, l, gl, pl, sl ; Secondary sounds: k, id On cover: Includes rhyming activity, key words and picture dictionary